An example of failure tolerant operation of a kinematically redundant manipulator - Maciejewski, Anthony A., author; Lewis, Christopher L., author; IEEE, publisher (Colorado State University. Libraries, 1994)
The high cost involved in the retrieval and repair of robotic manipulators used for remediating nuclear waste, processing hazardous chemicals, or for exploring space or the deep sea, places a premium on the reliability of the system as a whole. For such applications, kinematically redundant manipulators are inherently more reliable since the additional degrees of freedom (DOF) may compensate for a failed joint. In this work, a redundant manipulator is considered to be fault tolerant with respect to a given task if it is guaranteed to be capable of performing the task after anyone of its joints has failed and is locked in place. A method is developed for insuring the failure tolerance of kinematically redundant manipulators with respect to a given critical task. Techniques are developed for analyzing the manipulator's workspace to find regions which are inherently suitable for critical tasks due to their relatively high level of failure tolerance. Then, constraints are imposed on the range of motion of the manipulator to guarantee that a given task is completable regardless of which joint fails. These concepts are illustrated for a PUMA 560 that is used for a three-dimensional positioning task.
Keywords: position control; maintenance engineering; manipulators; kinematics; redundancy